Molluscs Attached To A Rocky Substrate In The Manado Mall Reclamation Area, Bahu Sub-District, Manado - Ni Luh Vegi Yulianti Yulianti; N. Gustaf F. Mamangkey Mamangkey; Indri Shelovita Manembu Manembu; Erly Y. Kaligis Kaligis; Medy Ompi Ompi; Suzanne Lydia Undap Undap; Marten Maxs Maxs (Masyarakat Moluska Indonesia, 2023)
Cyclophorus is one of the genera in terrestrial gastropods that inhabits forest floor, leaf litter, rocks, and decayed wood. This research aims to determine the morphological and anatomical characters of the genus Cyclophorus in Indonesia and its phenetic relationship. Descriptive method was applied by conducting observation on shell, operculum, as well as anatomical characters. Cluster analysis in Rstudio was conducted to analyze the morphological data and to see its phenetics relationship. Based on 214 shell and 21 genitalia, 12 Cyclophorus species and subspecies stored in the Museum Zoologicum Bogoriense (from the total of 20 species and subspecies in Indonesia) were identified. The morphological character of the Cyclophorus in Indonesia (shell and operculum) can be differentiated based on the shell shape, shell pattern, spiral bands, the number of whorls, shell diameter, and operculum. Diagnostic characters in the genitalia are the bursa copulatrix and oviduct (female), and penis (male). The cluster analysis shows the separation of adult shells and operculum into six (6) groups i.e. (1) C. nigricans from Sulawesi is allegedly a distinctive species of the eastern region in Indonesia; (2) C. rafflesii eximius from Sumatra and Java; (3) C. theobaldianus from Kalimantan; (4) C. rafflesii dan C. rafflesii rafflesii from Sumatra and Java; (5) C. schepmani and C. stevenabbasorum from Sumatra which an allegedly the typical species of Sumatra; and (6) C. tuba plicifera, C. tuba, C. perdix, C. perdix perdix and C. perdix borneensis from Sumatra, Java and Kalimantan.